Pembinaan UMKM Perempuan Desa Cikupa; Sinergi SDM dan Potensi Lokal menuju Kemandirian Ekonomi di Era Digital - Rina Masruroh; Wely Hadi Gunawan; Iqbal Arraniri (JAMARI : Jurnal Pengabdian Masyarakat Mandiri, 2026)
Empowerment of women-owned MSMEs in rural areas plays a vital role in supporting family and village economies. This community service activity aims to improve Human Resource (HR) capacity and economic independence of women MSME actors in Cikupa Village, Darma District, Kuningan Regency. The partners faced main obstacles such as low business management literacy, lack of business legality (NIB), and minimal use of digital technology for marketing. The implementation methods included socialization, business management training using the Business Model Canvas (BMC), assistance with business legality (OSS-RBA), and digital marketing training (social media and e-commerce). The results showed an increase in partners' understanding of good business governance. Additionally, participants were successfully assisted in issuing Business Identification Numbers (NIB) and started utilizing WhatsApp Business and social media to promote local potential products. The synergy between HR capacity strengthening and digital technology adoption has proven capable of encouraging women MSME actors in Cikupa Village to be more adaptive and competitive.